Fenol total, flavonoid, dan aktivitas antioksidan beras coklat germinasi dari beras hasil budidaya di Provinsi Lampung: Total Phenols, flavonoids, and antioxidant activity of germinated brown rice from cultivated rice in Lampung Province - Nirmagustina, Dwi Eva; Wirawati, Chandra Utami; Winarto (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2025)
Germination process is a methodÂ to increase the acceptability of brown rice. In addition,it will increase the contentÂ of brown rice bioactive components. This study's purpose is to determine the contentÂ of total phenol, flavonoids, and antioxidant activity of germinated brown rice in 3 rice varieties (Mentik Susu, Ciherang, and Pandan Wangi) which are grownÂ in Prov. Lampung. The treatment was designed in a completely randomized block design (CRBD) with 3 replications. The data was processed with variance to determine the effect of treatment on the parameters tested and continued with the Tukey test to determine the differences between treatments. The results showed the contentÂ of total phenol, flavonoids, and antioxidant activity of germinated brown rice were influenced by rice varieties and germination time. Germinated brown rice of Ciherang variety showed the highest flavonoid content and antioxidant activity, 16.27mgQE/g ex and 575.36 G/mL, respectively. Germination duration of 24 hours showed the highest contentÂ of total phenol, flavonoid, and antioxidant activity, respectively 4.81 mg GAE/g ex, 18.60 mg QE/g ex, and 613.88 G/mL.